IMPLEMENTATION OF STUDENT MANAGEMENT TO IMPROVE LEARNING DISCIPLINE - Noviardi, Dicky; Wahyudi, Apri; Adha, Muhammad Mona (Al-Mubtadi: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
This study aims to analyze the implementation of student management in improving students’ learning discipline at SD Negeri 2 Sinar Banten, Central Lampung, Indonesia. Learning discipline is an important component in elementary education because it supports students’ academic achievement, responsibility, punctuality, and behavioral development in school environments. Student management is considered a strategic effort in regulating student activities systematically through planning, implementation, supervision, and evaluation processes. This research employed a qualitative approach with a case study design involving 36 participants consisting of the principal, homeroom teachers, subject teachers, students, and parents. Data were collected through participatory observation, semi-structured interviews, and documentation analysis, while data analysis used the interactive model of Miles, Huberman, and Saldana through data condensation, data display, and conclusion drawing. The findings revealed that student management was implemented through five integrated components, namely discipline program planning, consistent rule enforcement, educational reward and punishment systems, continuous monitoring and evaluation, and active parental involvement. The implementation significantly improved students’ learning discipline as reflected in the reduction of student violations from 199 to 83 cases (58.3%), improvement in attendance rates from 84.4% to 91.4%, and increased discipline assessment scores from 61.2% to 86.7%. The study concludes that collaborative and systematic student management contributes positively to strengthening learning discipline in rural elementary schools and provides practical implications for educational management development.